Implementation of Sex Education for Elementary School Children Based on the Extension Program in Sidomakmur Village - Amanda Aulia Rahma; Tsabita Farras Azzahra; Putri Peni Nur Izzati; Mohamad Pramanda Salih; Nindy Parawansa; Hesti Khasanah; Almas Alwi Akbar; Suwahono Suwahono (Universitas Palangka Raya, 2024)
In Indonesia, sex education is an important part of education that aims to provide children with a proper understanding of the biological, psychological, and social aspects of sexuality. The purpose and benefits of this service are to improve the knowledge and understanding of elementary school children about basic sexuality, their reproductive health, and to help children recognize and prevent sexual harassment and violence that threaten them and indirectly reduce the number of sexual crimes in early childhood. With the community-based asset approach method (Asset Based Community Development-ABCD) which focuses on evaluating assets in the community that are considered as supporting steps to strengthen the community. data were collected by providing counseling in schools about early sexuality education. This paper presents a brief overview of the current situation of the implementation of sex education in Sidomakmur Village, Kendal Regency, Indonesia.